Identification and validation of biomarkers related to centrosome replication in ulcerative colitis based on bulk transcriptome, single-cell RNA sequencing and experiments - Yang, Zhenhuan; Wu, Xingxing; Luo, Lei; Wu, Xiuxia; Wang, Yuliang; Huang, Tingting; Dang, Zhongqin; Nie, Shanwen (Frontiers in Immunology, 2025)
BackgroundUlcerative colitis (UC) is a complex chronic inflammatory disease. Centrosome amplification (CA) has been implicated in UC pathogenesis, but its mechanistic role remains unclear. This study aimed to investigate the relevance of centrosome amplification-related genes (CARGs) in UC progression.MethodsUC and control samples, along with CARGs, were obtained from public databases. Differential expression analysis identified differentially expressed genes (DEGs) between UC and controls. Candidate genes were selected by intersecting DEGs with CARGs. Biomarker identification employed 11 machine learning algorithms, receiver operating characteristic (ROC) analysis, and expression validation. Functional insights were gained through gene set enrichment analysis (GSEA), immune infiltration profiling, and clustering analysis. Cellular expression patterns of biomarkers were also examined. Finally, biomarker expression in colonic mucosal tissue was validated by RT-qPCR, Western blot, and Immunohistochemistry.ResultsSix biomarkers—TEX11, SLC16A1, OVOL1, EDNRA, HEPACAM2, and SPIRE2—were identified. Enriched pathways associated with these genes included cell adhesion molecules (CAMs) and oxidative phosphorylation. Immune infiltration analysis revealed significant interactions between biomarkers and differential immune cells (DICs), such as neutrophils, in UC. Consensus clustering stratified UC samples into two clusters, with DICs including M0 macrophages showing significant correlations with biomarkers. Single-cell expression analysis highlighted undifferentiated and enteroendocrine cells as potentially key cell types in UC. Validation through animal and clinical experiments demonstrated downregulation of SLC16A1, OVOL1, TEX11, and HEPACAM2, alongside upregulation of EDNRA in colonic mucosa of UC compared to controls.ConclusionSix CARGs—TEX11, SLC16A1, OVOL1, EDNRA, HEPACAM2, and SPIRE2—were identified as potential biomarkers with significant implications in UC pathogenesis.